ANALISIS TINGKAT KEPUASAN PASIEN TERHADAP PENANGANAN TERAPI OKUPASI DI INSTALASI REHABILITASI MEDIK RSUP PROF. DR. R. D. KANDOU MANADO - Wongkar, Meilany D.; Gessal, Joudy; Angliadi, Leonard S. (e-CliniC, 2015)
Abstract: Medical rehabilitation aims to lessen the impact of a disability and enhance the ability of people with disabilities, therefore, they can be involved in social interaction. One of the rehabilitation treatments is occupation therapy which helps individuals by giving suggestions and enhancing independence. Quality is a dynamic condition which fills or surpass the expectations. Quality is closely related to costumers’ satisfaction. It encourages the costumers to create a strong bond of relationship. This study aimed to obtain patients’ satisfaction degree toward the implementation of occupation therapy in the Medical Rehabilitation Installation Prof. Dr. R. D Kandou Hospital, Manado. This was a descriptive observational study. Sampleds were collected by using purposive sampling. The result of the T Test analysis showed that there was a significant difference between before and after the therapy with a p value = 0.000. Based on the result of the satisfaction degree to the variable of expectation and reality, the average obatined was 7.9. Conclusion: Patients’ expectation degree was higher than the reality of service that they received.Keywords: medical rehabilitation, occupation therapy, patients satisfaction degree.Abstrak: Rehabilitasi medik bertujuan untuk mengurangi dampak keadaan cacat dan meningkatkan kemampuan penyandang cacat sampai interaksi sosial. Salah satu pelayanan rehabilitasi ialah terapi okupasi, yang membantu individu dalam memberi anjuran dan menjamin bantuan untuk meningkatkan kemandirian. Kualitas merupakan kondisi dinamis yang memenuhi atau melebihi harapan. Kualitas memiliki hubungan yang sangat erat dengan kepuasan pelanggan, yaitu kualitas memberikan suatu dorongan kepada pelanggan untuk menjalani ikatan hubungan yang kuat. Penelitian ini bertujuan untuk mengetahui gambaran tingkat kepuasan pasien terapi okupasi di Instalasi Rehabilitas Medik RSUP. Prof. Dr. R. D. Kandou. Penelitian ini bersifat deskriptif observasional. Pengambilan sampel dilakukan secara purposive sampling. Hasil analisis uji t menunjukkan terdapat perbedaan bermakna sebelum dan sesudah terapi dengan nilai p = 0,000. Berdasarkan hasil uji nilai tingkat kepuasan terhadap variabel harapan dan kenyataan menunjukkan perbedaan dengan nilai rata-rata 7,9. Simpulan: Nilai harapan pasien lebih besar dari kenyataan pelayanan yang mereka terima.Kata kunci: rehabilitasi medik, terapi okupasi, tingkat kepuasan pasien